Case Based Learning Methods In Mechanical Earth Moving Courses In Improving Learning Outcomes Of Students Of Building Engineering Education - Titof Tulaka (Departement of Mathematics Education, 2023)
This research aims to determine student learning outcomes in the Mechanical Earth Moving course using the application of case based learning methods in building engineering education classes. This research uses a Classroom action research design) carried out on students majoring in Building Engineering Education, Faculty of Engineering for the Mechanical Earth Moving course. This research design was adapted to the implementation of research in cycle 1 and cycle II in building engineering education classes. This research data comes from students, namely in the form of test results carried out by lecturers on students, while student activities are observed by lecturers during the lecture process. This data is verified and processed to obtain information on student success levels from student learning outcomes. The research results show that The learning outcomes using the case based learning method in cycle I were 35% or there were 9 students who completed classical learning, while in cycle II the percentage of student learning completion was 90%. Thus, the application of cased based learning methods can improve student learning outcomes in the Mechanical Earth Removal course in Building Engineering Education.